2005
DOI: 10.1152/ajpheart.00966.2004
|View full text |Cite
|
Sign up to set email alerts
|

Vascular adaptation to 4 wk of deconditioning by unilateral lower limb suspension

Abstract: Physical inactivity or deconditioning is an independent risk factor for atherosclerosis and cardiovascular disease. In contrast to exercise, the vascular changes that occur as a result of deconditioning have not been characterized. We used 4 wk of unilateral lower limb suspension (ULLS) to study arterial and venous adaptations to deconditioning. In contrast to previous studies, this model is not confounded by denervation or microgravity. Seven healthy subjects participated in the study. Arterial and venous cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
104
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(120 citation statements)
references
References 43 publications
13
104
1
1
Order By: Relevance
“…Furthermore, reductions in capacitance were reported in spinal cord-injury individuals compared to control subjects (Frieden et al 1987;Hopman et al 1994), which is mainly attributed to the muscle atrophy and the possible concomitant vascular atrophy in the paralyzed legs. After bed rest, compliance of the popliteal vein remained unaltered, which is in line with previous deconditioning studies, using unilateral limb suspension (Bleeker et al 2005a) or bed rest (Bonde-Petersen et al 1994;Melchior and Fortney 1993). A possible reason that compliance is maintained during bed rest in the present study is the isolated location of the popliteal vein.…”
Section: Bed Rest and Venous Functionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, reductions in capacitance were reported in spinal cord-injury individuals compared to control subjects (Frieden et al 1987;Hopman et al 1994), which is mainly attributed to the muscle atrophy and the possible concomitant vascular atrophy in the paralyzed legs. After bed rest, compliance of the popliteal vein remained unaltered, which is in line with previous deconditioning studies, using unilateral limb suspension (Bleeker et al 2005a) or bed rest (Bonde-Petersen et al 1994;Melchior and Fortney 1993). A possible reason that compliance is maintained during bed rest in the present study is the isolated location of the popliteal vein.…”
Section: Bed Rest and Venous Functionsupporting
confidence: 91%
“…(2004), who reported an unaltered tibial and gastrocnemial vein diameter after 90 days of bed rest. These findings do not correspond with the previous results of a decrease in cross-sectional area of the popliteal and femoral vein (Arbeille et al 1999(Arbeille et al , 2001) and the common result of a decreased venous volume variation after bed rest (Bleeker et al , 2005aChrist et al 2001;Louisy et al 1997). The arterial vascular system also presented diameter reductions after deconditioning (Bleeker et al 2005a, b;De Groot et al 2006), but these changes over time were remarkably larger than previously shown in the venous vascular system.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…6,7 In several pathological conditions, such as pulmonary 8 and systemic essential hypertension, 9 heart failure, 10,11 atherosclerosis, and obesity, 12 ET-1 plasma levels are elevated and contribute to the increased vascular tone observed in these disease states. In models of skeletal muscle deconditioning, such as unilateral limb suspension 13 and bed rest, 14 vascular tone is also increased. In the present study, we hypothesize that the elevated vascular tone in deconditioned muscles can be explained by an augmented contribution of ET-1.…”
mentioning
confidence: 99%
“…In both of our patients, the symptoms occurred during non-weight bearing and subsided after weight bearing was commenced. Unilateral lower limb suspension experiments in normal patients have shown an increase in flow mediated dilatation of arteries of the lower limb along with a decrease in venous capacitance [6]. This mechanism may explain the vascular changes which were more intense with the foot in the dependent positions.…”
Section: Discussionmentioning
confidence: 99%